Dissemination of agricultural technologies: A new approach for Uganda - Kasimiro, Ogwal; Wakulira M., Okello, J.; Kiyini, R.; Mwebaze, M.; Yiga, D. (RUFORUM, 2012)
Uganda with an estimated current population of 34 million has had many approaches to agricultural extension service delivery but has not realised its potential level of production and productivity in agriculture. One key gap in agricultural transformation has been the weak linkage between farmers, extension workers and research for effective technology transfer. The Government of Uganda in the National Development plan 2011/2015 identified this gap and a five year project, the Agricultural Technology and Agri-business Advisory Services (ATAAS) was formulated. The ATAAS project with five (5) components is being implemented by the National Agricultural Research Organisation (NARO) and National Agricultural Advisory Services (NAADS) which are agencies of the Ministry of Agriculture, Animal Industry and Fisheries (MAAIF). Within the first year of implementation of ATAAS, stakeholders priorities were generated, a number of adaptive research trials set in response to stakeholders needs, multiplication of planting materials undertaken and appropriate Multi-stakeholders Innovations Platforms (MSIPs) established. With support from all stakeholders and effective monitoring and evaluation conducted, ATAAS is expected to transform the agricultural sector of Uganda. However, there is need to have stronger farmer, extension and research linkages for effective technology dissemination. Responsive adaptive research trials should be established with farmers actively participating and extension workers fully guided for better results. The establishment of functional Multistakeholders Innovations Platforms forms an effective tool in the value chain development of commodities and hence must be stressed. This will need to be underpinned by a strong human capital base to drive the process.
Keywords: NAADS; Research linkage; Technology transfer; Uganda